การเพิ่มปริมาณคำศัพท์วิชาการในการเขียนงานวิจัย (BOOSTING ACADEMIC WORDS IN RESEARCH WRITING) - เหมเชื้อ แสงจันทร์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2015)
บทคัดย่อ คุณลักษณะเฉพาะของคำศัพท์วิชาการซึ่งเป็นคำที่แสดงกระบวนการ การวิเคราะห์ และการประเมินผล ทำให้คำศัพท์วิชาการเป็นส่วนสำคัญในการเขียนรายงานการวิจัย งานวิจัยครั้งนี้มีจุดประสงค์เพื่อกระตุ้นให้นักศึกษาระดับบัณฑิตศึกษาใช้คำศัพท์วิชาการในการเขียนงานวิจัยมากขึ้นโดยใช้ “กระบวนการสังเกตคำ” และ “แนวลึกขั้นตอนการเรียนรู้คำ” ในช่วง 4 เดือนของการทดลอง นักศึกษาได้ใช้โปรแกรม AWL highlighter เพื่อกระตุ้นการสังเกตคำ จากนั้นศึกษาการใช้คำศัพท์ที่เลือกในคลังศัพท์ BNC Corpus เพื่อการศึกษาแนวลึก ผลการวิจัยพบว่า คำศัพท์วิชาการในการเขียนงานวิจัยฉบับปรับปรุงของนักศึกษามีปริมาณเพิ่มขึ้นเล็กน้อย Abstract The common features of academic vocabulary (process, analysis and evaluation) give rise to the need for implementing academic vocabulary in research writing. This study aimed to stimulate EFL postgraduates to increase the use of academic words in their research writing. ‘Word noticing process’ and ‘depth of processing words’ were implemented to foster academic vocabulary use. During the four-month course, participants used the AWL highlighter programme to identify academic words in their research projects and studied the use of selected academic words in the online British National Corpus (BNC) for deep processing. Results showed a slight increase in the quantity of academic words in the revised research reports.